Developing an mHealth program to improve HIV care continuum outcomes among young Black gay and bisexual men - Aaron Plant; Paul Sparks; Deborah Neffa Creech; Ta'Jalik Morgan; Jeffrey D. Klausner; Cornelis Rietmeijer; Jorge A. Montoya (BMC, 2024)
Abstract Background Young Black gay and bisexual men (YBGBM) in the United States face significant disparities in HIV care outcomes. Mobile health (mHealth) interventions have shown promise with improving outcomes for YBGBM across the HIV care continuum. Methods We developed an mHealth application using human-centered design (HCD) from 2019-2021 in collaboration with YBGBM living with HIV and with HIV service providers. Our HCD process began with six focus groups with 50 YBGBM and interviews with 12 providers. These insights were used to inform rapid prototyping, which involved iterative testing and refining of program features and content, with 31 YBGBM and 12 providers. We then collected user feedback via an online survey with 200 YBGBM nationwide and usability testing of a functional prototype with 21 YBGBM. Results Focus groups and interviews illuminated challenges faced by YBGBM living with HIV, including coping with an HIV diagnosis, stigma, need for social support, and a dearth of suitable information sources. YBGBM desired a holistic approach that could meet the needs of those newly diagnosed as well as those who have been living with HIV for many years. Program preferences included video-based content where users could learn from peers and experts, a range of topics, a community of people living with HIV, and tools to support their health and well-being. Providers expressed enthusiasm for an mHealth program to improve HIV care outcomes and help them serve clients. Rapid prototyping resulted in a list of content topics, resources, video characteristics, community features, and mHealth tools to support adherence, retention, goal setting, and laboratory results tracking, as well as tools to help organization staff to support clients. Online survey and usability testing confirmed the feasibility, acceptability, and usability of the content, tools, and features. Conclusions This study demonstrates the potential of a video-based mHealth program to address the unique needs of YBGBM living with HIV, offering support and comprehensive information through a user-friendly interface and videos of peers living with HIV and of experts. The HCD approach allowed for continuous improvements to the concept to maximize cultural appropriateness, utility, and potential effectiveness for both YBGBM and HIV service organizations.